STRUKTUR DAN DISTRIBUSI PENDAPATAN SERTA TINGKAT KESEJAHTERAAN PETANI KELAPA SAWIT RAKYAT DI KABUPATEN TULANG BAWANG - Reki Septian Patra; Raden Hanung Ismono; Adia Nugraha (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2019)
This research aims to analyze the income structure, income distribution, and household welfare level of palm oil smallholders in Tulang Bawang Regency. This research used a survey method. The study sample consisted of 54 independent palm oil farmers in Penawar Tama Sub-District and 22 independent palm oil farmers in Gedung AjiBaru Sub-District. Data were collected in July - August 2017 and analyzed using quantitative and qualitative descriptive analysis. The results showed that the income structures of palm oil smallholders consist of contribution from on farm income, which is the highest, i.e. 55.10 percent in scenario 1 and 49.11 percent in scenario 2. The following income sources are from non farm, and off farm activities respectively. The household income of palm oil smallholders is relatively evenly distributed in scenario 1 with Gini Index of 0.17 which shows low inequality, and distributed in the medium category in scenario 2 with a Gini Index of 0.31 which shows moderate inequality. The level of welfare of palm oil smallholdersaccording to Sajogyo (1997) criteria shows that the majority of farmers are categorized as poor and almost poor, reaching 68.42 percent. According to the Badan Pusat Statistik (2014) shows that the majority of palm oil smallholdersis categorized as not prosperous (64.47 percent), and the rest is in prosperous category.Key words: farming, income, oil palm, welfare